The role of immunometabolism in macrophage polarization and its impact on acute lung injury/acute respiratory distress syndrome - Wang, Lian; Wang, Dongguang; Zhang, Tianli; Ma, Yao; Tong, Xiang; Fan, Hong (Frontiers in Immunology, 2023)
Lung macrophages constitute the first line of defense against airborne particles and microbes and are key to maintaining pulmonary immune homeostasis. There is increasing evidence suggesting that macrophages also participate in the pathogenesis of acute lung injury (ALI)/acute respiratory distress syndrome (ARDS), including the modulation of inflammatory responses and repair of damaged lung tissues. The diversity of their functions may be attributed to their polarized states. Classically activated or inflammatory (M1) macrophages and alternatively activated or an-ti-inflammatory (M2) macrophages are the two main polarized macrophage phenotypes. The precise regulatory mechanism of macrophage polarization is a complex process that is not com-pletely understood. A growing body of literature on immunometabolism has demonstrated the essential role of immunometabolism and its metabolic intermediates in macrophage polarization. In this review, we summarize macrophage polarization phenotypes, the role of immunometabo-lism, and its metabolic intermediates in macrophage polarization and ALI/ARDS, which may represent a new target and therapeutic direction.